Determinant Factors of Customers Switching Behavior to Customer Satisfaction and Loyalty in Online Transportation Users in Bandung - Suryawardani, Bethani; Wulandari, Astri (JDM (Jurnal Dinamika Manajemen), 2020)
This study was aimed to find out which factors that become the most influence on customers switching behavior for online transportation and how the impact on their satisfaction and loyalty for future consumption. Transportation service is one of the service industry sectors that play a strategic role in human life. The intense competition in the online transportation industry and the various choice of brands in the market make the consumers easy to switch from their current product to other brand products. The research method used in this study was a quantitative method, with Structural Equation Modeling (SEM) analysis technique using SMART PLS 2.0 software. The sampling method used was accidental sampling with 400 respondents. The results of the study showed that the contribution of price, promotion and e-service quality simultaneously influenced on which directly affected customer satisfaction was 64.9%. Whereas, the results of the study also showed the contribution of price, promotion, e-service quality and customer satisfaction simultaneously influenced on which directly affected customer loyalty was 48.3%. E-service quality has the biggest impact on customer satisfaction by 30.69%; meanwhile,Â  promotion has the biggest impact on loyalty by 3.17%.